An XML model for electronic services. (10th May 2006) - Vassilakis, Costas; Lepouras, George; Halatsis, Constantin; Lobo, Tomas Pariente
With the need for electronic services to be developed and deployed more and more rapidly, it is imperative that concrete models of electronic services are developed, to facilitate systematic work of electronic service stakeholders, concrete semantics, and coherent representations across services developed within an organisation. Using the XML language to develop such a model offers a number of additional advantages, such as rich semantics, facilitation of data interchange, extensibility, high abstraction levels, and possibility for mechanical processing. In this paper, we present the design aspects of an XML model for electronic services, which has been used for building a repository of interlinked elements representing e-services. A web-based interface for the management of this repository and a tool for automatically compiling e-service descriptions into executable images have been developed alongside. The model has been evaluated by a mixture of electronic service stakeholders, and the results of this evaluation are also presented.